Ensuring the rights of the personality in criminal proceedings - Kuanaliyeva, G.A.; Yerezhepkyzy, R. (Journal of actual problems of jurisprudence, 2018)
Ensuring the rights of the personality is especially actual in the sphere of criminal trial, as in this sphere of imperious activity of government bodies, essential restrictions and even constitutional violations cases, the right of the personality arise and are shown. Here application of various measures of criminal procedure coercion, including measures of restraint which significantly limit the rights and legitimate interests of the personality, involved in the sphere of criminal justice possibly. Key words: personality, rights and freedoms of the person, concept, legal policy.